Fatores socioeconômicos da criminalidade no Estado de São Paulo: um enfoque da economia do crime - Mariano, Rodrigo Silva (2010)
The present paper aims at to supply empiric evidences of the impact of the variables socioeconomics in the level of crimes against the patrimony (crimes against property of many individuals and corporations) in the cities of the State of São Paulo for the year of 2000. For so much an analysis is accomplished on the economical literature of the crime, based on Becker (1968) and Ehrlich (1973). This paper analysis, still, several studies accomplished in Brazil concerning the problem of the criminality, pointing the effects of the variations of the variables socioeconomics in the level of criminality of several types, among them, the crimes against the patrimony, objective of this paper. Of this it sorts things out, search to revise the several authors' contributions that study the problem of the criminality and empiric results that collaborate in the analysis of the determinant of the criminality for the several municipal districts of the State of São Paulo to appear. Through an analysis econometric adopting the Method of Ordinary Square Minimal (MQO) this work analyzed through some varied the behavior of the determinant of the criminality. The obtained results are suitable with the literature base of the economy of the crime and it points that the variables socioeconomics can explain the variation partly in the levels of crimes against the patrimony in the studied municipal districts